Characterization and Antibacterial Activity of Cu doped ZnO Thin Film Prepared by Sol-Gel Dip Coating Method and Phytosynthesized Zinc Oxide Nanoparticles from Senna alata and Euphorbia hirta - Sumalatha, R.; Sivakumar, M.; Parthasarathy, G. (Asian Journal of Chemistry, 2022)
Zinc oxide nanoparticles exhibit significant antibacterial activity. The present study focused on determining the antibacterial activity of green synthetic zinc oxide nanoparticles (ZnO NPs) and Cu doped ZnO thin film. The prepared ZnO NPs and Cu doped ZnO films were characterized by XRD analysis, SEM, FTIR and UV-vis. Amorphous and nano cluster shapes were observed in SEM analysis. The presence of different chemical functional groups was confirmed by FTIR analysis. The optical properties Cu doped ZnO nanostructures were analyzed by UV-visible analysis. The results clearly confirmed the efficient synthesis of spherical ZnO nanoparticles with average size range from 40 to 50 nm. The Cu doped ZnO thin films and ZnO nanoparticles showed dose-dependent antibacterial activity against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Salmonella typhi and Pseudomonas aeruginosa. The IC50 value was calculated as approximately 60 μg/mL. Growth kinetics studies were performed in the presence of ZnO nanoparticles demonstrated the bacteriostatic effect of ZnO nanoparticles.